2007
DOI: 10.1097/01.sla.0000254370.29893.e4
|View full text |Cite
|
Sign up to set email alerts
|

CDH1 Truncating Mutations in the E-Cadherin Gene

Abstract: CDH1 mutations in individuals from families with HDGC are associated with gastric cancer in a highly penetrant fashion. CDH1 mutations are an indication for total gastrectomy in these patients. This mutation will identify patients with cancer before other detectable symptoms or signs of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(36 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…These recently identified gene mutations are symptomatically identified by diffuse gastric carcinoma, endometrial cancer, ovarian cancer, and lobular breast carcinomas 5558. Lifetime risks for these mutations (chromosome 16q) are approximately 70%–80% for gastric cancer and 40%–60% for breast carcinomas in women 59,60. The prognosis of upper gastric carcinomas is poor, with only a 10% survival rate over a 5-year period, decreasing to 4% for total stomach involvement 55,57.…”
Section: E-cadherin Hereditary Diffuse Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These recently identified gene mutations are symptomatically identified by diffuse gastric carcinoma, endometrial cancer, ovarian cancer, and lobular breast carcinomas 5558. Lifetime risks for these mutations (chromosome 16q) are approximately 70%–80% for gastric cancer and 40%–60% for breast carcinomas in women 59,60. The prognosis of upper gastric carcinomas is poor, with only a 10% survival rate over a 5-year period, decreasing to 4% for total stomach involvement 55,57.…”
Section: E-cadherin Hereditary Diffuse Gastric Cancermentioning
confidence: 99%
“…The prognosis of upper gastric carcinomas is poor, with only a 10% survival rate over a 5-year period, decreasing to 4% for total stomach involvement 55,57. Compiling information on this rare disease has shown that around 25%–30% of hereditary diffuse gastric cancers are associated with a familial mutation in the CDH1 gene 59,60. Reduced life expectancy is assumed, as undiagnosed late-stage gastric cancer has a high mortality rate of <20% 5-year survival 60,61.…”
Section: E-cadherin Hereditary Diffuse Gastric Cancermentioning
confidence: 99%
“…Although a number of genetic alterations have been identified in gastric cancer, including those in cadherin 1 (CDH1) (8,9), β-catenin (10), CDH17 (11) and Met (12), no study has distinguished these alterations by anatomical subsite. A number of previous gene expression profiling studies have also ignored the differences in diverse anatomical subsite (11,13,14), such as in GCA and GNCA.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, about 100 CDH1 mutation positive families have been reported [14]. Because of the high risk of developing gastric cancer and the limited value of surveillance for high-risk lesions, prophylactic gastrectomy is advised to mutation carriers in these families [12,18]. Despite the small proportion of gastric cancer patients that originate from HDGC families, identification of these families is important in order to initiate preventive measures in these high risk individuals.…”
Section: Environmental and Inherited Factorsmentioning
confidence: 99%